A Randomized Controlled Phase 3 Study on the Efficacy and Safety of Recombinant Human Growth Hormone in Children With Idiopathic Short Stature - Yuan, Jinna; Fu, Junfen; Wei, Haiyan; Zhang, Gaixiu; Xiao, Yanfeng; Du, Hongwei; Gu, Wei; Li, Yanhong; Chen, Linqi; Luo, Feihong; Zhong, Yan; Gong, Haihong (Frontiers in Endocrinology, 2022)
Background To evaluate the safety and efficacy of daily somatropin (Jintropin®), a recombinant human growth hormone, in prepubertal children with ISS in China. Methods This study was a multicenter, randomized, controlled, open-label, phase 3 study. All subjects were randomized 3:1 to daily somatropin 0.05 mg/kg/day or no treatment for 52 weeks. A total of 481 subjects with a mean baseline age of 5.8 years were enrolled in the study. The primary endpoint was change in (△) height standard deviation score (HT-SDS) for chronological age (CA). Secondary endpoints included △height from baseline; △bone age (BA)/CA; △height velocity (HV) and △insulin-like growth factor 1 (IGF-1 SDS). Results △HT-SDS at week 52 was 1.04 ± 0.31 in the treatment group and 0.20 ± 0.33 in the control group (P < 0.001). At week 52, statistical significance was observed in the treatment group compared with control for △height (10.19 ± 1.47 cm vs. 5.85 ± 1.80 cm; P < 0.001), △BA/CA (0.04 ± 0.09 vs. 0.004 ± 0.01; P < 0.001), △HV (5.17 ± 3.70 cm/year vs. 0.75 ± 4.34 cm/year; P < 0.001), and △IGF-1 SDS (2.31 ± 1.20 vs. 0.22 ± 0.98; P < 0.001). The frequencies of treatment-emergent adverse events (TEAEs) were similar for the treatment and the control groups (89.8% vs. 82.4%); most TEAEs were mild to moderate in severity and 23 AEs were considered study-drug related. Conclusions Daily subcutaneous administration of somatropin at 0.05 mg/kg/day for 52 weeks demonstrated improvement in growth outcomes and was well tolerated with a favorable safety profile. Trial Registration: ClinicalTrials.gov (identifier: NCT03635580). URL: https://clinicaltrials.gov/ct2/show/NCT03635580